Developing Board Game to Improve Students’ Grammar Mastery of The Eleven Grade Students of SMKN 4 Malang - Moh Mario Alvin Supandhi; Putu Dian Danayati Degeng; Hasbulah Isnaini (Jurnal Pendidikan : Riset dan Konseptual, 2022)
A board game is a type of play where participants follow defined rules. A board games as the utilization of games to support teaching and learning grammar. Board games that incorporate curriculum content or other educational material are referred to as educational games (Michel, 2016). Educational games can be considered as an example of these fun-based teaching methods. This study uses Research and Development (R&D) design, it develops supplementary material for helps students to learning grammar. The product was designed through adopted stages of development from Akker (1999). The researcher found every aspect of the board game in this research then can be used as upplementary material for students have more knowledge on how to arrange a word by word to make a apropriate sentence, how to learn about tenses, how to make a teamwork with partner, how to handle certain situation and also how to develop themselves better as a student will be. In this addition, the researcher discussed the material of the the product. The first step was preliminary stage the researcher used SMKN 4 Malang as a place of observation. Second, the formative evaluation phase or analysis stage, the researche was interviewing a english teacher in SMKN 4 Malang to know the problem of students to learning grammar. The third step was prototyping. In this step, the researcher design the product (TANGAMES board game) An expert give the feedback to product. The product is validated by expert to make sure that the product meets the requirements needed as a proper teaching media that can be used in teaching process. After feedbacks received, the product then will be tested in SMKN 4 Malang. Next stage is interviewing, Some students will be interviewed by the research to know the effectiveness of the product. Last stage, product will be revised and adjusted as needed.